2005
DOI: 10.1111/j.1464-410x.2005.05626.x
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernia repair with polypropylene mesh during radical retropubic prostatectomy: an easy and practical approach

Abstract: maximum size 15 ¥ 7.5 cm and a small slit on its medial side was then created and placed in the preperitoneal space, embracing the spermatic cord and covering the myopectinal orifice. Preoperative risk factors, e.g. constipation, pulmonary disease or urinary obstructive symptoms, were collected retrospectively from the files. Complications after surgery, including wound infection, pelvic collections, urinary fistula and recurrence of the hernia, were assessed. RESULTSPreoperative risk factors for hernia develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Prostatectomy, both transurethral or retropubic, and combined hernia repair is a well described and accepted procedure, which decreases the number of operations, anesthesia, hospital stay and health costs, and does not increase operative and postoperative morbidity 4–7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostatectomy, both transurethral or retropubic, and combined hernia repair is a well described and accepted procedure, which decreases the number of operations, anesthesia, hospital stay and health costs, and does not increase operative and postoperative morbidity 4–7 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prevalence of inguinal or umbilical hernias during pregnancy is about 1:2000, 3 these being usually treated a few weeks after delivery. While hernia repair combined with prostatic surgery is a well reported common practice, with no increased postoperative morbidity, 4–6 the results of hernia repair combined with gynecological surgery have neither been extensively analyzed or carried out, and simultaneous completions of hernia repairs and of cesarean sections at the end of pregnancy are even less described.…”
Section: Introductionmentioning
confidence: 99%
“…The result of hernia correction with a simultaneous Stoppa procedure and open surgical simple prostatectomy was associated with wound infection. 26 Reducing surgical cuts can be associated with a lower wound infection rate. A retrospective study by Choi et al showed that in 48 hernia repairs using the preperitoneal approach with a 12-cm mesh, no hernia recurrence was seen in comparison with the no-mesh group.…”
Section: Discussionmentioning
confidence: 99%
“…In 1876, Annandale [17] described the preperitoneal hernioplasty and subsequently the modification of this technique by Nyhus (cited in [4]) was popularized and widely used. The preperitoneal mesh repair described by Stoppa et al [18] was reported by urologists performing RRP to give good results [4,19]. Choi et al [4] reported 70 hernioplasties using the preperitoneal approach; 35 had a mesh repair and the other 35 did not.…”
Section: Discussionmentioning
confidence: 99%